2016
DOI: 10.1111/mmi.13313
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis using 13C‐glycerol and other carbon tracers reveals a bipartite metabolism of Legionella pneumophila

Abstract: Amino acids represent the prime carbon and energy source for Legionella pneumophila, a facultative intracellular pathogen, which can cause a life-threatening pneumonia termed Legionnaires' disease. Genome, transcriptome and proteome studies indicate that L. pneumophila also utilizes carbon substrates other than amino acids. We show here that glycerol promotes intracellular replication of L. pneumophila in amoeba or macrophages (but not extracellular growth) dependent on glycerol-3-phosphate dehydrogenase, GlpD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(111 citation statements)
references
References 68 publications
5
106
0
Order By: Relevance
“…Furthermore, during exponential growth, SpoT acts as a ppGpp hydrolase, which keeps the concentration of the alarmone low (67). In a previous study, we showed that the metabolism of serine results in a high rate of fatty acid biosynthesis (28), and thus, the SpoT-dependent cellular levels of ppGpp are likely decreased under these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, during exponential growth, SpoT acts as a ppGpp hydrolase, which keeps the concentration of the alarmone low (67). In a previous study, we showed that the metabolism of serine results in a high rate of fatty acid biosynthesis (28), and thus, the SpoT-dependent cellular levels of ppGpp are likely decreased under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This is substantiated by the following findings: (i) inositol (and not a "secondary product") is metabolized, as intracellular growth promotion by the carbohydrate is dependent on iolT or iolG, (ii) inositol reaches the LCV after phagosome closure and pathogen vacuole formation, since the compound promotes growth when added several hours after infection, (iii) the fluorescent glucose analogue 2-NBDG accumulates in vacuoles harboring strain JR32 but not icmT mutant bacteria, and (iv) glycerol and glucose also reach LCVs during intracellular growth of L. pneumophila in A. castellanii (28). Noteworthy, compared to LCVs, 50% fewer vacuoles harboring icmT (or rpoS) mutant bacteria accumulate 2-NBDG, indicating that vacuole remodelling by a functional Icm/Dot T4SS is required for carbohydrate transport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations